The effect of unrelated social exchanges on facial attractiveness judgments - Faust, Natalie T. (2020)
Whereas the influence of facial attractiveness (FA) on social judgments has been well documented, much less is known about the converse influence of social exchanges on FA judgments. Previous research has shown that social dimensions inherently related to the face judged, such as status, can affect such judgments. However, we found that facial attractiveness ratings were affected by social exchanges unrelated to the face judged. In three experiments, we examined how competitive and cooperative financial exchanges influence subsequent facial aesthetic judgments. Compared to cooperation, competition decreased women's (but not men's) ratings of men's facial attractiveness; this pattern of effects also occurred for ratings of buildings, suggesting that competition suppressed aesthetic appreciation. However, women's responses to women's faces followed an inverse pattern, as competition (rather than cooperation) elevated women faces’ attractiveness ratings. Introducing self-affirmation, a psychological mechanism that alleviates the effects of social competition, restored attractiveness ratings. This finding suggests that women's own-gender judgments in a competitive environment are affected by a perception of threat induced by social comparison. Overall, this study suggests that aesthetic judgments are not immune to social conditions. Such moderating effects contribute to our understanding of how sociocultural environments dynamically regulate aesthetic preferences.